2012
DOI: 10.1016/j.ajpath.2012.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia Is Associated with Alterations in DNA Methylation of Genes Involved in Collagen Metabolism

Abstract: Maternal vascular dysfunction is a hallmark of preeclampsia. A recently described vascular phenotype of preeclampsia involves increased expression of matrix metalloproteinase-1 (MMP-1) in endothelial cells, vascular smooth muscle, and infiltrating neutrophils. In contrast, the expression of tissue inhibitor of metalloproteinases-1 (TIMP-1) and collagen type Iα 1 is either reduced or not changed in the vessels, suggesting an imbalance in vessel collagen degradation and synthesis in preeclampsia. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Hence, these factors might be contributing to poor migration and proliferation of the endothelial cells and poor development of new blood vessels. The observed high expression of MMP2 in maternal blood in preeclampsia is consistent with the documented high level of MMP2 in preeclamptic plasma (Myers et al 2005) and might have a role in regulating vascular tone, as highlighted by a recent study that suggested the role of MMP1 expression in vasoconstriction (Mousa et al 2012). Consistent with our results, high levels of TIMP1 and TIMP2 have been demonstrated in preeclamptic endothelial cells (Merchant et al 2004).…”
Section: Discussionsupporting
confidence: 80%
“…Hence, these factors might be contributing to poor migration and proliferation of the endothelial cells and poor development of new blood vessels. The observed high expression of MMP2 in maternal blood in preeclampsia is consistent with the documented high level of MMP2 in preeclamptic plasma (Myers et al 2005) and might have a role in regulating vascular tone, as highlighted by a recent study that suggested the role of MMP1 expression in vasoconstriction (Mousa et al 2012). Consistent with our results, high levels of TIMP1 and TIMP2 have been demonstrated in preeclamptic endothelial cells (Merchant et al 2004).…”
Section: Discussionsupporting
confidence: 80%
“…Matrix alterations in the maternal vasculature have recently been implicated in preeclampsia. MMP-1 was found to be hypomethylated in omental arteries from preeclamptic women, and 5-Aza treatment induced MMP-1 mRNA expression and protein secretion in cultured human vascular SMC [63]. …”
Section: Role Of Epigenetics In Regulating Smc Plasticitymentioning
confidence: 99%
“…The alterations in DNA methylation of MMP8 gene were found in preeclampsia, a disease in which dizziness is one of the symptoms. Mousa et al [2012] showed that DNA hypomethylation significantly increased MMP-8 expression. The promoter regions of the MMP1 and MMP8 genes have reduced methylation in the omental arteries of preeclamptic women compared with those of normal pregnant women.…”
Section: Discussionmentioning
confidence: 99%